Aluminum stress in Crotalaria spp.: anatomic changes, antioxidative response and nutrition - Beatriz Silvério dos Santos; Tassia Caroline Ferreira; Patrícia Fernanda Rosalem; Maiara Luzia Grigoli Olivio; Valentina Pasquali Bossardi; Aline Redondo Martins; Lucas Anjos Souza; Liliane Santos de Camargos (Plant Stress)
Species of the genus Crotalaria (Fabaceae) are widely distributed in tropical and subtropical regions, standing out for their rapid growth, high biomass production, and adaptation to low-fertility soils. The Al3+ion, predominant in soils with a pH below 5.2, is highly toxic, causing anatomical changes in roots and leaves, compromising water and nutrient absorption. The aim of this study was to evaluate the anatomical and physiological responses of C. juncea, C. spectabilis, and C. ochroleuca cultivated in soil with a high Al3+content (0.5 cmolc dm-3). The study was conducted in a randomized block design with a 2 × 3 factorial scheme, with or without Al in the soil and three Crotalaria species, with five replications. The results demonstrate specific acclimation strategies: C. juncea stood out for its high antioxidant activity (SOD and MDA) and magnesium concentration; C. ochroleuca exhibited adaptation associated with root anatomical characteristics and increased N and P concentrations; while C. spectabilis showed responses related to leaf anatomy and antioxidant enzymes (CAT and POX). These observations highlight distinct mechanisms of Al3+tolerance, contributing to the management of agricultural crops in acidic soils and reinforcing the potential of Crotalaria species as allies in sustainable agricultural practices in diverse environments.